Origin of δ13C minimum events in thermocline and intermediate waters of the western South Atlantic. (15th November 2021) - Nascimento, R.A.; Santos, T.P.; Venancio, I.M.; Chiessi, C.M.; Ballalai, J.M.; Kuhnert, H.; Govin, A.; Portilho-Ramos, R.C.; Lessa, D.; Dias, B.B.; Pinho, T.M.L.; Crivellari, S.; et al.
Abstract: Stable carbon isotopic (δ 13 C) minimum events have been widely described in marine archives recording the properties of thermocline and intermediate waters during glacial terminations. However, the mechanisms associated with these events remain ambiguous. Here we present three high temporal resolution deep-dwelling planktonic foraminifera δ 13 C records from the main thermocline and one benthic δ 13 C record from the modern core of Antarctic Intermediate Water (AAIW). Our sediment cores are distributed along the western South Atlantic from the equator to the subtropics, with the longest record spanning the last ∼300 kyr. The results show that δ 13 C minimum events were pervasive features of the last three glacial terminations and Marine Isotope Stage 4/3 transition in the western South Atlantic. Two distinct mechanisms were responsible for the δ 13 C minima at the thermocline and intermediate depths of the Atlantic, respectively. We suggest that the δ 13 C minimum events at the thermocline were mostly driven by the thermodynamic ocean-atmosphere isotopic equilibration, which is supported by calculated δ 13 C of dissolved inorganic carbon in the subtropical western South Atlantic as well as by previously published model simulations. On the other hand, intermediate depths δ 13 C minimum events in the tropics were likely caused by the slowdown of the Atlantic meridional overturning circulation and the associated accumulation of isotopically light carbon at mid and intermediate depths of the Atlantic Ocean. Highlights: We investigated δ 13 C minimum events in the western South Atlantic. δ 13 C minima occurred in the upper ocean over the last three glacial terminations. Thermodynamic equilibration drives δ 13 C minima at the thermocline. AMOC slowdown drives δ 13 C minima at intermediate depth of the tropical Atlantic.